THE EFFECT ON PEER TEACHING METHOD TOWARD STUDENTS’ WRITING SKILL IN NARRATIVE TEXT AT THE GRADE X STUDENTS MA PP NURUL HUDA KULIM JAYA - Yanti, Tiyas Kartini Apri; Syaftinentias, Widi; Yolanda, Rizky; Juli Ayuri, Sati (Ensiklopedia of Journal, 2025)
Language skills have four components, namely listening skill, speaking skill, reading skill, and writing skill. The four skills are closely related. Students must learn these four skills. If students cannot master these four components of language properly and correctly, it will affect their language skills as well. Writing skills are especially important today (Puspita, 2017). Teaching writing requires the most talent and continuous practice. It is no less important than listening, reading, and speaking skills. Writing is a productive skill (Helaluddin & Awalludin, 2020). This means a person's writing skills can be well developed if continually honed and trained.Writing skills are a skill that is used to communicate indirectly, not face-to-face with others (Helaluddin & Awalludin, 2020).  Meanwhile, there is another opinion that writing is a productive skill using writing (Helaluddin & Awalludin, 2020).  Writing is said to be the most complicated language skill. This is because writing is copying words and sentences and developing thoughts in an orderly writing structure.Learning writing skills at MA PP Nurul Huda Kulim Jaya, especially class X students in the second semester of the new teaching, namely writing narrative texts. A narrative text is a story essay presenting a series of events arranged chronologically according to the time sequence (Helaluddin & Awalludin, 2020).  The event can happen, but it can also be imaginary. Generally, essays or narrative texts aim to entertain readers with aesthetic experiences through stories, both fiction and nonfiction. It can be seen that students have low skills in writing narrative texts. The above situation may be influenced by the methods used so far. For this reason, researchers try to apply one of the other learning methods to create fun learning, of course, with fun methods.